Interface microstructural and mechanical properties of Al/Mg bimetal composites fabricated by friction stir additive manufacturing - Wenxin Zhang; Yang Chen; Mingxing Han; Long Li; Ashish Kumar; Song Gao; Chuansong Wu; Lei Shi (Journal of Materials Research and Technology)
The pursuit of lightweight and high-strength structural design has become a critical objective in aerospace, shipbuilding, automotive, and other manufacturing industries. Al/Mg bimetal composites combine the high strength, corrosion resistance, and machinability of Al alloys with the low density and high stiffness of Mg alloys, offering significant application potential. This study investigates single-layer multi-track and multi-layer single-track friction stir additive manufacturing (FSAM) of Al/Mg composites. Surface morphology, macro/microstructure, mechanical properties, and fracture behavior were analyzed. Under optimal FSAM parameters (600 rpm, 75 mm/min, 3 mm pin length), the maximum tensile strength reached 215 MPa (transverse) and 220 MPa (longitudinal). The intermetallic compound (IMC) layer thickness decreased from the first to the fourth track due to reduced thermal cycling. In multi-layer FSAM (Mg–Al–Mg arrangement), IMC thickness at the Al/Mg interface exceeded that at the Mg/Al interface due to reheating effects. Furthermore, microhardness measurements indicate a hierarchical distribution: top Mg > bottom Mg > middle Al. It proves that the FSAM is a suitable method for fabricating Al/Mg bimetal composites. These findings provide valuable insights into the microstructural evolution and mechanical performance of Al/Mg bimetal composites in additive manufacturing, contributing to their broader industrial application.